H. SYEKH OESMAN SAHABUDDIN SEBAGAI TOKOH AGAMA DI BAGANSIAPIAPI TAHUN 1924-1946 - Dea Andhiny; Isjoni Isjoni; Bedriati Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The name H. Syekh Oesman Sahabuddin is popular for the people of Rokan Hilir Regency, as the syekh is the role model for the people. Although he is gone, his name still remembered for the community of Rokan Hilir, especially in Bagansiapiapi. In his dedication for Bagansiapiapi he had the students who already had the Khalipah title or ch in Bagansiapiapi, he taught fikih, hadist, tasawuf and taught Naqsabandiyah tarekat. Not only teaches fikih, hadist and tarekat, he is also active in giving islamic recitations in some places in Bagansiapiapi, in the suluk that he also built as the center of his teaching. The purpose of this study is to identify the overall Biography of H. Syekh Oesman Sahabuddin, How the process of spreading islamic in teaching fikih, hadist and Naqsabandiyah tarekat, then method he taught his students in the suluk that he was built. Using a qualitative approach, a type of research whose findings are obtained through statistical procedures or other forms of calculation. The type of research is field research, which is the research done by plunging into the field to explore and examine data related to the title. The respondents in this study were the grandchildren of H. Syekh Oesman Sahabuddin and the close people of H. Syekh oesman Sahabuddin who still in Bagansiapiapi. While the data collection technique in this research is done using two methods: interview and documentation study. The results show that H. Syekh Oesman Sahabuddin has a great role in advancing education in the science of fikih, hadist, tasawuf in Bagansiapiapi.Key Words: H. Syekh Oesman Sahabuddin, figure, Religion, Bagansiapiapi